CytR Homolog of Pectobacterium carotovorum subsp. carotovorum Controls Air-Liquid Biofilm Formation by Regulating Multiple Genes Involved in Cellulose Production, c-di-GMP Signaling, Motility, and Type III Secretion System in Response to Nutritional and Environmental Signals - Haque, M. M.; Oliver, M. M. H.; Nahar, Kamrun; Alam, Mohammad Z.; Hirata, Hisae; Tsuyumu, Shinji (Frontiers in Microbiology, 2017)
Pectobacterium carotovorum subsp. carotovorum [Pcc (formerly Erwinia carotovora subsp. carotovora)] PC1 causes soft-rot disease in a wide variety of plant species by secreting multiple pathogenicity-related traits. In this study, regulatory mechanism of air-liquid (AL) biofilm formation was studied using a cytR homologue gene deletion mutant (∆cytR) of Pcc PC1. Compared to the wild type (Pcc PC1), the ∆cytR mutant produced fragile and significantly (P<0.001) lower amounts of AL biofilm on salt-optimized broth plus 2% glycerol (SOBG), yeast peptone dextrose adenine, and also on King’s B at 27°C after 72 h incubation in static condition. The wild type also produced significantly higher quantities of AL biofilm on SOBGMg—(magnesium deprived) containing Cupper (Cu2+), Zinc (Zn2+), Manganese (Mn2+), Magnesium (Mg2+) and Calcium (Ca2+) compared to the ∆cytR mutant. Moreover, the wild type was produced higher amounts of biofilms compared to the mutant while responding to pHs and osmotic stresses. The ∆fliC (encoding flagellin), flhD::Tn5 (encoding a master regulator) and ∆motA (a membrane protein essential for flagellar rotation) mutants produced a lighter and more fragile AL biofilm on SOBG compared to their wild counterpart. All these mutants resulted in having weak bonds with the cellulose specific dye (Calcofluor) producing lower quantities of cellulose compared to the wild type. Gene expression analysis using mRNA collected from the AL biofilms showed that ∆cytR mutant significantly (P<0.001) reduced the expressions of multiple genes responsible for cellulose production (bcsA, bcsE and adrA), motility (flhD, fliA, fliC and motA) and type III secretion system (hrpX, hrpL, hrpA and hrpN) compared to the wild type. The CytR homologue was therefore, argued to be able to regulate the AL biofilm formation by controlling cellulose production, motility and T3SS in Pcc PC1. In addition, all the mutants exhibited poorer attachment to radish sprouts and AL biofilm cells of the wild type was resistant than stationary-phase and planktonic cells to acidity and oxidative stress compared to the same cells of the ∆cytR mutant. The results of this study therefore suggest that CytR homologue is a major determinant of Pcc PC1’s virulence, attachment and its survival mechanism.